Youth Community Engagement: A Recipe for Success - Mary E. Arnold; Brooke Dolenc; Elissa E. Wells (The University of Alabama, 2022)
This article describes how community engagement contributes to youth development. Drawing on the literature on youth engagement, youth development, and youth-adult partnerships, the authors examine a successful community youth engagement program that engages youth and their adult partners in a participatory evaluation project that results in community action. The research emphasizes the important role of youth-adult partnerships in community youth engagement projects and outlines strategies for success.